Pendidikan Karakter Dalam Perspektif Psikologi Transpersonal Islam - Shifa Rifkiana (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2021)
The problem in this study is the lack of research that links character education to the psychology of transpersonal Islam. To discuss the matter, the purpose of this research is to know the education of character in psychology in general and in the psychological perspective of transpersonal Islam. Transpersonal psychology tries to link with a higher soul, a transatory experience, which in time imbues knowledge by intuition and comes to true nature. And that true nature is the recognition of a higher soul. In this case is god. In Islam, it means god.